2023
DOI: 10.3389/fmicb.2023.1158130
|View full text |Cite
|
Sign up to set email alerts
|

Field scale biodegradation of total petroleum hydrocarbons and soil restoration by Ecopiles: microbiological analysis of the process

Abstract: Ecopiling is a method for biodegradation of hydrocarbons in soils. It derives from Biopiles, but phytoremediation is added to biostimulation with nitrogen fertilization and bioaugmentation with local bacteria. We have constructed seven Ecopiles with soil heavily polluted with hydrocarbons in Carlow (Ireland). The aim of the study was to analyze changes in the microbial community during ecopiling. In the course of 18 months of remediation, total petroleum hydrocarbons values decreased in 99 and 88% on average f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…Martínez-Rivera & Cardona-Gallo, (2021) also found that their biostimulation treatments decreased alpha diversity of the polluted soil, due to the increase of Actinobacteria filum in treated soils. Our results also agreed with the effect of bioaugmentation in Ecopiles shown byMartínez-Cuesta et al, (2023), besides in this case the predominance between the different families of bacteria changes during a year of monitoring obeying to environmental changes These studies provide consistent testimonies that are advocating the potential of bioaugmentation application, as a promising technique capable to perform biological treatment of hydrocarbon contaminated soil and other matrices. All these studies also highlight the environmentally friendly nature, efficacy, and potential scalability of bioaugmentation for environmentally friendly, sustainable, efficient and low-cost solutions.…”
supporting
confidence: 89%
“…Martínez-Rivera & Cardona-Gallo, (2021) also found that their biostimulation treatments decreased alpha diversity of the polluted soil, due to the increase of Actinobacteria filum in treated soils. Our results also agreed with the effect of bioaugmentation in Ecopiles shown byMartínez-Cuesta et al, (2023), besides in this case the predominance between the different families of bacteria changes during a year of monitoring obeying to environmental changes These studies provide consistent testimonies that are advocating the potential of bioaugmentation application, as a promising technique capable to perform biological treatment of hydrocarbon contaminated soil and other matrices. All these studies also highlight the environmentally friendly nature, efficacy, and potential scalability of bioaugmentation for environmentally friendly, sustainable, efficient and low-cost solutions.…”
supporting
confidence: 89%